2016
DOI: 10.1177/1932296816632543
|View full text |Cite
|
Sign up to set email alerts
|

Technology Use in Transition-Age Patients With Type 1 Diabetes

Abstract: Youth with chronic illnesses have the greatest risk for a decline in their health management during transition-age. Because of this demonstrated and well-known issue, research has focused on how to improve the transition of care process. Despite the increasing number of technological devices on the market and the advances in telemedicine modalities available to patients with type 1 diabetes (T1D), the utilization of technology is still suboptimal among patients of transition-age (ages 13-25). This article revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 55 publications
(94 reference statements)
1
23
0
Order By: Relevance
“…6 Efforts to improve health outcomes in this population have focused on developing new systems of care that may improve the transition between pediatric and adult medicine. 5 Our study is the first to evaluate the societal cost-effectiveness of the CoYoT1 care model, a combination of telemedicine and shared medical appointments, compared to usual care in transition-age young adults with T1D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Efforts to improve health outcomes in this population have focused on developing new systems of care that may improve the transition between pediatric and adult medicine. 5 Our study is the first to evaluate the societal cost-effectiveness of the CoYoT1 care model, a combination of telemedicine and shared medical appointments, compared to usual care in transition-age young adults with T1D.…”
Section: Discussionmentioning
confidence: 99%
“…1 The transition period from pediatric to adult care is challenging and frequently accompanied by missed clinic visits and suboptimal glycemic control. [2][3][4][5][6] An innovative care model -shared medical appointments delivered through home telehealth -was evaluated by the recent Colorado Young adults with T1D (CoYoT1) trial. The trial demonstrated that the care model improved patient attendance and diabetes care engagement.…”
Section: Introductionmentioning
confidence: 99%
“…As identified, adolescence is a life transition which is notorious for reduced compliance with treatment, particularly with long term conditions Los et al, 2016). Burke & Dowling (2007) identified it as being a period where young people are still maturing emotionally and cognitively and it is associated with independence, new experiences and testing of boundaries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The consequence of this reduction in effective diabetes management and engagement with services during adolescence is directly associated with a deterioration in health (Lostein et al, 2013;Merrick, et al, 2015;Campbell et al, 2016;Los et al, 2016). Thynne et al (2014) agree that the transition to adult services is a difficult time, and professionals working in primary care should aim to ease transition for adolescents to improve responsiveness to increase autonomy, independence and responsibility.…”
Section: Service Related Transitionmentioning
confidence: 99%
See 1 more Smart Citation